Multiannual, intensive strength-endurance training modulates the activity of the cardiovascular and autonomic nervous system among rowers of the international level - Kowalik, T.; Klawe, J. J.; Tafil-Klawe, M.; Slomko, W.; Slomko, J.; Srokowska, A.; Lewandowski, A.; Zalewski, P. (BioMed Research International, 2019)
Introduction. Professional athlete training is significantly different from recreational physical activity, and sustained, repetitive exposure to over-strenuous and intensive training may result in critical changes of most systems and organs in a sportsman's body. Aim. The assessment of the influence of multiannual strength-endurance training on the autonomic nervous system (ANS) and cardiovascular system (CVS) among the rowers of Polish national team. Materials and Methods. 20 rowers, aged 20-30, seniors of Polish national team were qualified into the study. The functional examination of ANS was conducted by means of Task Force® Monitor system. The assessed parameters included hemodynamic parameters, heart rate, and blood pressure variability and reflexes sensitivity of baroreceptors. In order to examine and compare the reaction of autonomic nervous system the subjects underwent a tilt test. Results. In the study group, significantly higher levels of sBP (129.3 ± 12.2 vs 118.3 ± 8.4, ), SI (59.9 ± 8.8 vs 41.2 ± 6.8, ), CI (3.2 ± 0.5 vs 2.4 ± 0.4, ), and significantly lower levels of HR (54.2 ± 5.3 vs 60.1 ± 5.7, ) and TPRI (2333.3 ± 389.9 vs 2950.2 ± 604.2, ) compared to the control group, were found. After the tilt test the levels of HR () and TPRI () were significantly higher but SI () and CI () were significantly lower in the study group compared to the control. Conclusions. Multiannual strength-endurance training connected with rowing activities substantially modulates the activity of cardiovascular and autonomic nervous system, influences the volumetric workload of the heart and structural changes, and increases the sensitivity of reflexes of arterial baroreceptors.